2016
DOI: 10.1016/j.jaci.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of food allergy

Abstract: The past few decades have witnessed an increase in the prevalence of IgE-mediated food allergy (FA). For prevention strategies to be effective, we need to understand the causative factors underpinning this rise. Genetic factors are clearly important in the development of FA, but given the dramatic increase in prevalence over a short period of human evolution, it is unlikely that FA arises through germline genetic changes alone. A plausible hypothesis is that 1 or more environmental exposures, or lack thereof, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
140
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 99 publications
2
140
0
5
Order By: Relevance
“…Among the 98 participants with positive peanut SPT responses at entry, 35.3% of the avoidance group and 10.6% of the consumption group had peanut allergy at 60 months of age (P = .004; a 24.7% absolute risk reduction and a 70% relative risk reduction in the prevalence of peanut allergy, resulting in a number needed to treat of 4). The LEAP-on study [24] demonstrated that the benefits achieved in the LEAP trial persisted when LEAP trial peanut consumers subsequently avoided peanut for 1 year from 60 to 72 months of age. This indicates that the oral tolerance achieved in the LEAP trial was durable.…”
Section: Balance Of Benefits and Harmsmentioning
confidence: 99%
“…Among the 98 participants with positive peanut SPT responses at entry, 35.3% of the avoidance group and 10.6% of the consumption group had peanut allergy at 60 months of age (P = .004; a 24.7% absolute risk reduction and a 70% relative risk reduction in the prevalence of peanut allergy, resulting in a number needed to treat of 4). The LEAP-on study [24] demonstrated that the benefits achieved in the LEAP trial persisted when LEAP trial peanut consumers subsequently avoided peanut for 1 year from 60 to 72 months of age. This indicates that the oral tolerance achieved in the LEAP trial was durable.…”
Section: Balance Of Benefits and Harmsmentioning
confidence: 99%
“…20 The inclusion of an aggressive eczema treatment strategy distinguished the PETIT study from the other clinical trials and thus this was a likely explanation for the difference in results. 23 An earlier randomised controlled trial of 118 Japanese drive forward discovery science and clinical practice. This will inevitably require dedicated investments of resources but the payback for implementing a successful strategy could be substantial public health gains.…”
Section: What Is New In Allergy Prevention That Could Impact On Hong mentioning
confidence: 99%
“…The prevalence of food allergy reactions, which range in severity from relatively mild features to life-threatening anaphylaxis, has been estimated as affecting up to 7% of children and 6% of adults [1][2][3][4][5][6] and is currently considered as a global public health problem. 7,8 The clinical diagnosis of food allergy primarily involves skin testing 9,10 and blood (serum) analysis.…”
Section: Introductionmentioning
confidence: 99%